2013
DOI: 10.1111/os.12066
|View full text |Cite
|
Sign up to set email alerts
|

Management of Great Vessels and Nerves in Limb‐Salvage Surgery for Bone and Soft Tissue Tumors

Abstract: In recent years, limb-salvage surgery has gradually replaced amputations and become one of the main treatment strategies for patients with bone and soft tissue tumors of the extremities. The goals of tumor resection in limb-salvage surgery are to reduce the recurrence rate and preserve as much limb function as possible. However, depending on the size and specific location of the tumor, large neurovascular bundles may be involved. In addition, management of large nerves and vessels can make wide marginal resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Autologous vein grafts, therefore, are preferred for young patients. Although the need for simultaneous venous reconstruction is controversial [18], we performed venous reconstruction with a GSV graft in this patient. No postoperative edema of the distal limb occurred, and the reconstructed vein remained patent through the final follow-up at 20 months.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous vein grafts, therefore, are preferred for young patients. Although the need for simultaneous venous reconstruction is controversial [18], we performed venous reconstruction with a GSV graft in this patient. No postoperative edema of the distal limb occurred, and the reconstructed vein remained patent through the final follow-up at 20 months.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the inguinal region, the medial thigh compartment, and the popliteal fossa are common sites of lower limb STS with vascular involvement. 7 The reported frequency of major vascular involvement varies between 5% and 10% of all adult patients with STS of the lower extremity, with femoral vessels being reported as the most commonly involved vascular structures followed by the inguinal and popliteal vessels. [8][9][10] En bloc tumour resection, with resection of the great vessels, has been reported in up to 5.0% of all patients with lower extremity sarcomas.…”
Section: Authorsmentioning
confidence: 99%
“…[8][9][10] En bloc tumour resection, with resection of the great vessels, has been reported in up to 5.0% of all patients with lower extremity sarcomas. 7,[11][12][13] In contrast, nerve resection was carried out in only 1.2% of cases of lower limb STS with neural involvement, according to a study by Brooks et al 14 In a recent study, however, sciatic nerve involvement was reported at 15.0% of all lower limb STS, with 4.5% of all cases of lower extremity STS requiring complete nerve resection. 15 In this article, the authors aim to review the current literature regarding the multidisciplinary management of lower limb STS, with a focus on diagnostic and therapeutic management strategies of major neurovascular involvement.…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For STS with vascular involvement, reasonable oncological outcomes have been reported with vessel reconstruction in limb-salvage surgery [ 9 – 11 ]. Nerve reconstruction, on the other hand, does not guarantee preservation of function [ 12 ]. Tumor infiltration of the sciatic nerve has previously been an indication for limb amputation [ 13 ], but more recent studies have shown limb-sparing surgery with partial or complete sciatic nerve resection to be an excellent alternative [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%